Adenocarcinoma of the Rete Testis: Clinicopathologic and Immunohistochemical Characterization of 6 Cases and Review of the Literature. (May 2019) - Al-Obaidy, Khaleel I.; Idrees, Muhammad T.; Grignon, David J.; Ulbright, Thomas M.
Abstract : Adenocarcinoma of the rete testis is rare and its etiological and pathologic characteristics are not well studied. We therefore investigated the clinical, morphologic, and immunohistochemical features of 6 cases diagnosed at our institution and conducted a detailed review of the literature. The mean age was 64 years. All patients presented with testicular masses; 4 were right-sided. On gross examination, all tumors were centered in the hilum and had solid and cystic cut surfaces. Microscopically, all had intrarete and invasive growth and showed multiple patterns, with a variable proportion of papillary, solid and glandular morphology, the latter varying from slit-like lumens to well-formed glands and tubules. Less common patterns included corded/trabecular (n=3), cribriform (n=3), glomeruloid (n=3), nested (n=2), and micropapillary (n=2). Discrete nests of eosinophilic and clear cells were a distinctive feature in 3 cases. Geographic necrosis occurred in 3 cases. All showed at least moderate nuclear pleomorphism with ovoid nuclei. Transition from benign to malignant rete epithelium was seen in all cases. The stroma was hyalinized to partially fibrotic. On immunohistochemical study, the tumor cells were positive for CK7 (5/5), AE1/AE3 cytokeratin (5/5), EMA (5/5), vimentin (5/5), EpCAM (detected by BerEP4 anitbody) (4/5), CK5/6 (4/5), nuclear Wilms Tumor-1 (4/5), epithelial specific antigen (detected by MOC31 antibody) (3/4), PAX8 (3/5), and calretinin (2/5). OCT3/4, SALL4, CD30, NKX3.1, PSA, α-inhibin, CK20, and S100 protein were negative. Ki-67 proliferative index ranged from 5% to 60% (mean: 40, median: 43). At presentation, 5 patients had retroperitoneal lymph node metastasis and one of these also had pulmonary metastases. The sixth patient developed pulmonary metastasis within 15 months of diagnosis. Three died within 4 years of diagnosis. In summary, adenocarcinoma of the rete testis is a rare malignant tumor with poor survival and a high propensity for retroperitoneal lymph node metastasis that must be distinguished from other testicular neoplasms and metastasis to the testis. Hilar localization, transition from benign to malignant rete epithelium, and supportive immunostains aid its accurate diagnosis. Abstract : Supplemental Digital Content is available in the text.